Influence of Pedagogical Content Knowledge on Teacher Trainee Professional Competency at University of Nairobi, Kenya - Lilian, Ganira Khavugwi; Amollo, Odundo Paul (American Journal of Education and Learning, 2019)
Teaching as a knowledge-based profession requires pedagogical content knowledge for problem-solving, decision making, class management and sensitivity for adapting to diverse needs of learners. Whereas teacher knowledge is absolutely a component of professionalism, pedagogical content knowledge contributes to mastery of teaching, self-regulation and cognitive abilities for professional competence. Further, pedagogical content knowledge assists teacher trainees to; reflect on experiences; express insights about anticipated practice and develop appropriate ways of communicating during instructional delivery. This study explored influence of pedagogical content knowledge and teaching practice assessment process at the University of Nairobi. Anchored on descriptive survey design, the study targeted 68 trainee teachers on teaching practice from 17 Counties sampled randomly. The study used interview schedules, observation guides and documentary analysis to collect data from trainee teachers. For data analysis, the study relied on descriptive and inferential statistics, with data presented using tables. The study results found inconsistencies in the manner in which teacher trainees prepared for teaching practice. Recommendations advocate for teacher educators to re-examine appropriate preparation approaches that can assist teachers to prepare effectively for instructional management. Further, the University of Nairobi should explore appropriate and reliable mechanisms for sustaining and financing teaching practice process in order to achieve professional competence.